Problem Finding in Professional Learning Communities: A Learning Study Approach. Issue 2 (3rd March 2016) - Tan, Yuen Sze Michelle; Caleon, Imelda Santos
Abstract : This study marries collaborative problem solving and learning study in understanding the onset of a cycle of teacher professional development process within school-based professional learning communities (PLCs). It aimed to explore how a PLC carried out collaborative problem finding—a key process involved in collaborative problem solving—that has received minimal attention in the extant literature. In line with this goal, we adopted the learning study approach, which highlights the application of a theory in research lessons. Multiple data sources were drawn upon to construct a narrative description of four consecutive meetings, detailing challenges and turning points that teachers experienced while engaged in collaborative problem finding, and how the process was facilitated by developing shared understandings of the complexity of possible curricular problems and establishing a common ground amongst teachers. Other modes of action and factors that can facilitate the process of collaborative problem finding are also presented.